Eficiencia y eficacia del programa de abastecimiento de medicamentos del Hospital Belén de Trujillo - 2017 - Huaman Castillo, Juan Felix (2018)
The efficiency and effectiveness of the medication supply program of the Belén de Trujillo Hospital - 2017 was evaluated. Allowing to evaluate the degree of efficiency and effectiveness; 40 tracer drugs selected among the most demanded in the health services were used and represent proportionally to the population in number of pharmaceutical products included in the National List of Essential Medicines; For this purpose, the frequency was measured using the following indicators: 1. Weighted average percentage of variation in inventory, 2. Average percentage of time of stock-outs, 3. Average percentage of a set of 40 tracer drugs not expired available. From the analysis of the results, the following is concluded: (1.) The efficiency in the store of the supply program of the Belén de Trujillo Hospital is 0.81%; finding difference for: loratadine 10 mg. (2.) The efficiency through the average percentage of the shortage time is 3.75%; finding difference for: Acetylcysteine 600 mg tablet, Atorvastatin (as calcium salt) 20 mg tablet, Atorvastatin (as calcium salt) 40 mg tablet, Epinephrine (as hydrochloride or tartrate) 1 mg / 1mL injection, Lidocaine hydrochloride 10 g 2 g / 100g gel presenting 16.6%; Carbamazepine 200 mg tablet, Cephalexin 500 mg tablet, Chlorpromazine hydrochloride 100 mg tablet, Diazepam 2 mL 5 mg / ml injection with 8.3%; and for Vancomycin (as hydrochloride) 500 mg injection. it was 33.3%. (3.) The effectiveness through the average percentage of a set of 40 tracer drugs not expired available in the SISMED Program, is 100%